2007
DOI: 10.1177/1076029607302567
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Recombinant Activated Factor VII (NovoSeven) in Three Cases of Uncontrolled Bleeding Caused by Disseminated Intravascular Coagulopathy

Abstract: Recombinant activated factor VII has been used successfully in many cases of traumatic and surgical bleeding complications that were unresponsive to standard treatment. However, because disseminated intravascular coagulation can develop from a thrombin burst as a side effect of recombinant activated factor VII, it is not yet established for bleeding complications induced by disseminated intravascular coagulation. This article presents 3 patients with severe sepsis and fulminant disseminated intravascular coagu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Neutrophil elastase, which is released during sepsis, can degrade tissue factor pathway inhibitor, the inhibitor of the TF pathway, which may further enhance coagulation . Furthermore, case studies reported that FVII consumption and uncontrolled bleeding during sepsis can be reduced and survival improved by systemic administration of additional FVIIa . Occurrence of diffuse pulmonary bleeding can be reduced by local administration of FVIIa into the airspace of the lung…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophil elastase, which is released during sepsis, can degrade tissue factor pathway inhibitor, the inhibitor of the TF pathway, which may further enhance coagulation . Furthermore, case studies reported that FVII consumption and uncontrolled bleeding during sepsis can be reduced and survival improved by systemic administration of additional FVIIa . Occurrence of diffuse pulmonary bleeding can be reduced by local administration of FVIIa into the airspace of the lung…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with rFVIIa (Eptacog alfa activated) may be helpful to alleviate severe bleeding in these patients. 104,105 Treatment with rFVIIa might be beneficial in patients with impaired platelet function, a possible side effect, potentially due to DIC-associated platelet exhaustion or treatment with various drugs, including nonsteroid anti-inflammatory drugs and antibiotics. Recombinant FVIIa has been shown to of interest in the management of obstetrical DIC secondary to placental abruption or amniotic fluid embolism and other conditions associated with severe peripartum hemorrhage.…”
Section: Therapeutic Strategies For Dicmentioning
confidence: 99%
“…72 However, in the clinical scenario of life-threatening hemorrhage (e.g., maternal postpartum hemorrhage complicated by DIC, neonatal necrotizing enterocolitis) the use of rFVIIa was described by others and us with varying success in achieving hemostasis. 22,[73][74][75] Our recommendation is to limit the use of rFVIIa to rescue attempts in scenarios of catastrophic acutely life-threatening hemorrhage in which conventional measures to achieve hemostasis have failed.…”
Section: Human Protein Cmentioning
confidence: 99%